Academic leaders’ role in developing entrepreneurship in postgraduate students of Saudi Arabia public universities - Mofareh Alkrdem (Cogent Education)
This study examines the integration of entrepreneurship programs within postgraduate studies at Saudi public universities and explores the role of academic leaders in developing entrepreneurship skills among postgraduate students. Using a descriptive research design, the study surveyed 922 postgraduate students from the Colleges of Education at various Saudi public universities. The findings revealed statistically significant differences in the effectiveness of academic leaders’ roles in developing entrepreneurship skills across different groups of students. Based on these results, the study recommends that universities organize targeted seminars and workshops on entrepreneurship skills and innovative thinking to encourage students to engage in entrepreneurial behaviours. This research contributes to the field of education by highlighting the critical role that academic institutions and their leaders play in cultivating entrepreneurship skills, thereby promoting independence and self-reliance among postgraduate students. The study underscores the importance of embedding entrepreneurship education into postgraduate curricula to better prepare students for the demands of a dynamic, entrepreneurial economy.